Concentration of vasoactive intestinal polypeptide, neuropeptide Y and calcitonin gene related peptide in neoplastic tissue of the human large intestine - Godlewski, Janusz; Pidsudko, Zenon; Sienkiewicz, Waldemar (Contemporary Oncology/Współczesna Onkologia, 2011)
Aim of the study : The purpose of this study was to investigate the presence of vasoactive intestinal polypeptide (VIP), neuropeptide Y (NPY) and calcitonin gene related peptide (CGRP) neuropeptides in neoplastic tissue of the large intestine. The results obtained were compared to an unchanged part of the intestine originating from the same patient. Material and methods : The tissue samples were taken from the postoperative part of the intestine, resected during an operation due to treatment of colon cancer. Tissues were taken from 15 patients. Concentrations of neuropeptides were determined by ELISA tests, and results were calculated per 1 γ of fresh tissue. The data obtained were statistically analysed. Results : In tissues of the neoplastic tumour of the sigmoid colon and rectum the concentration of VIP and NPY was determined (28.9 ng/g and 8.6 ng/g, respectively). The observed values were statistically significantly lower than those observed in corresponding tissues of unchanged intestinal segments (83.9 ng/g for VIP and 19.5 ng/g for NPY). Surprisingly, amounts of CGRP were very similar in both neoplastic and intact tissues (13.3 ng/g and 13.4 ng/g respectively). Conclusions : Immunoenzymatic investigations allow one to establish the concentration of neuropeptides associated with the enteric nervous system in cancer tissues of the large intestine. Various concentrations of these neuropeptides were observed in particular patients of both compared groups. The performed statistical analysis did not reveal associations between degree of cancer infiltration within the colonic wall and the level of presence of investigated neuropeptides in either cancer or control tissues. The fact of presence of these neuropeptides in cancer tissues confirmed by this study should be underlined at the same time.